Amphimela raydahensis sp. nov. from the Kingdom of Saudi Arabia (Coleoptera: Chrysomelidae: Galerucinae: Alticini) - Torkey, Ashraf M. El; Dhafer, Hathal M. Al (Zootaxa, 2015)
Amphimela raydahensis sp. nov. is described from Garf Raydah Nature Reserve (Abha, Asir Province), southwestern Kingdom of Saudi Arabia. This species was collected using black light traps at different elevations dominated by cacti and wild olive trees. This is the first confirmed species of Amphimela known from the Arabian Peninsula.